Understanding the ion-induced elongation of silver nanoparticles embedded in silica - Peña Rodríguez, Ovidio (2017)
In this work we have studied the elongation of silver nanoparticles irradiated with 40 MeV Bromine ions by means of in situ optical measurements, transmission electron microscopy and molecular dynamics simulations. The localized surface plasmon resonance of silver nanoparticles has a strong dependence on the particle shape and size, which allowed us to obtain the geometrical parameters with remarkable accuracy by means of a fit of the optical spectra. Optical results have been compared with transmission electron microscopy images and molecular dynamics simulations and the agreement is excellent in both cases. An important advantage of in situ measurements is that they yield an extremely detailed information of the full elongation kinetics. Final nanoparticle elongation depends on a complex competition between single-ion deformation, Ostwald ripening and dissolution. Building and validating theoretical models with the data reported in this work should be easier than with the information previously available, due to the unprecedented level of kinetic details obtained from the in situ measurements.